KAJIAN BUDAYA KERJA PEGAWAI KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Mahwandi . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The main concern of this article is about work culture of employee in Samboja. It was relating to authority and responsibility in finishing their duty. There are some indicators that influence work culture, such as the degree of understanding, cooperations among them, discipline, and work order. The result of this reseacrh find that leadership and work environment play significant role in supporting a positive work culture implementation.